FMICW radar simulator - Mandlík Michal; Brázda Vladimír (IEEE (Institute of Electrical and Electronics Engineers), 2015)
The main goal of the paper is to develop a Frequency Modulation Interrupted Continuous Wave radar simulator. The radar frequency is 35.4 GHz and it is intended to detect clouds. The simulated output data are compared with output data acquired by the real radar. The real data are acquired from the observation of a static object – a chimney. Radar Cross Section (RCS) of the chimney is calculated and used for simulations. RCS value is used in the simulation for better approximation result. Paper contains a method for detection based on Power Spectral Density.
Simulátor FMICW radaru
Keywords: FMICW; radar; STFT; continuous wave; simulator; RCS; FMICW; radar; STFT; stálá vlna; simulátor; RCS